The Picture so Far: 50 Years of Painting Conservation - García Fernández-Villa, Silvia (Ge-conservacion, 2018)
The Picture so Far: 50 Years of Painting ConservationAbigail Granville, Laura Hinde, Sophie Plender, Hayley Tomlinson, Nancy Wade (eds)London: Archetype Publications Ltd, 2017ISBN: 9781909492240Dimensiones: 6.3 x 0.5 x 9.3Páginas: 156Ilustraciones en color